(untitled) (Bangladesh Journal of Agricultural Research, 2013)
The fully matured pumpkins (Cucurbita moschata Poir) of BARI Pumpkin-1 and BARI Pumpkin-2 were harvested from the experimental field of Horticulture Research Centre, BARI, Gazipur, Bangladesh. They were then stored under ambient room conditions (27-31 °C and 75-90% RH) for various periods ranged from 15 days to 120 days. The effect of different storage periods was assessed by evaluating their impact on changes in quality attributes of pumpkins. Results indicated that a slow but steady weight loss occurred in pumpkin with maximum loss of 18 and 21% after 120 days of storage in BARI Pumpkin-1 and BARI Pumpkin-2, respectively. ?-carotene and ascorbic acid contents were decreased throughout the whole storage time, however, they were drastically reduced during first 30 days of storage. Total soluble solids content increased until 45 days of storage followed by a decrease with progress in time. Titratable acidity was slowly decreased and simultaneously pH value was increased throughout the storage period. The results indicated that storage conditions need to be managed carefully to slow down any changes in fresh pumpkin. Bangladesh J. Agril. Res. 38(2): 247-255, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15888